2020
DOI: 10.34067/kid.0000352019
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Secular Trends of Cardiovascular, Nutritional, and Inflammatory Markers in Patients on Hemodialysis

Abstract: Background All life on earth has adapted to the effects of changing seasons. The general and ESKD populations exhibit seasonal rhythms in physiology and outcomes. The ESKD population also shows secular trends over calendar time that can convolute the influences of seasonal variations. We conducted an analysis that simultaneously considered both seasonality and calendar time to isolate these trends for cardiovascular, nutrition, and inflammation markers. Methods We used data from adult patients on hemodialysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In the majority of patients, the roxadustat dosing algorithm achieved and/or maintained Hb at target. The influences of Hb cycling 34 and the effects of seasonality 35 are also anticipated and can influence the need for dose titration over time. Nonetheless, when considering the time in range for Hb levels within 10–12 g/dL, roxadustat use in the present study appeared consistent with injectable ESAs reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of patients, the roxadustat dosing algorithm achieved and/or maintained Hb at target. The influences of Hb cycling 34 and the effects of seasonality 35 are also anticipated and can influence the need for dose titration over time. Nonetheless, when considering the time in range for Hb levels within 10–12 g/dL, roxadustat use in the present study appeared consistent with injectable ESAs reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…According to one theory, being exposed to low temperatures causes a rapid release of catecholamines, which in turn causes increases in platelet aggregability, vasomotor tone, hemodynamic parameters, and other hematological and endothelial parameters. When a person comes from warm indoor to cold circumstances, the resultant increase in heart workload and oxygen consumption may precipitate an ACS [30,31].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%